A simulation‐based resident‐as‐teacher program: The impact on teachers and learners. Issue 12 (15th July 2015) - Miloslavsky, Eli M.; Sargsyan, Zaven; Heath, Janae K.; Kohn, Rachel; Alba, George A.; Gordon, James A.; Currier, Paul F.
Abstract : BACKGROUND: Residency training is charged with improving resident teaching skills. Utilizing simulation in teacher training has unique advantages such as providing a controlled learning environment and opportunities for deliberate practice. OBJECTIVE: We assessed the impact of a simulation‐based resident‐as‐teacher (RaT) program. DESIGN: A RaT program was embedded in an existing 8‐case simulation curriculum for 52 internal medicine (IM) interns. Residents participated in a workshop, then served as facilitators in the curriculum and received feedback from faculty. METHODS: Residents' teaching and feed back skills were measured using a pre‐ and post‐program self‐assessment and post‐session and post‐curriculum evaluations by intern learners. SETTING/PARTICIPANTS: Forty‐one second‐ and third‐year residents participated in the study August 2013 to October 2013 at a single center. RESULTS: Pre‐ and post‐program teaching skills were assessed for 34 of 41 resident facilitators (83%) participating in 3.9 sessions on average. Partaking in the program led to improvements in resident facilitators' self‐reported teaching and feedback skills across all domains. The most significant improvement was in teaching in a simulated environment (2.81 to 4.16, P < 0.001). Interns rated the curriculum highly (81% "excellent, " 19% "good") and reported that resident facilitators frequently utilized debriefing techniques covered in the RaT program. CONCLUSIONS: Our simulation‐based RaT program offered a unique opportunity for deliberate practice of teaching skills in a controlled environment and led to improvements in resident facilitators' teaching and feed back skills. The simulation curriculum, facilitated by residents, was well received by the intern learners. Our program design may serve as a model for the development of simulation curricula and RaT programs within IM residencies. Journal of Hospital Medicine 2015;10:767–772. © 2015 Society of Hospital Medicine